CENTRALIDADE FORMAL DO PLANO DIRETOR NO PLANEJAMENTO DAS CIDADES BRASILEIRAS E O DIREITO A CIDADE: contradições e desafios pertinentes a São Luís (MA/Brasil). - COSTA, Lila Barbosa (2019)
Analysis of the relationship between the Master Plan and the right to the city in Brazilian particularity, based on the recognition that, without considering the aggravation of the urban issue, this urban policy instrument, as provided for in the City Statute (Federal Law No. 10.257 / 2001) persists as guiding of the planning and the municipal urban management in the direction of the realization of this right in cities of Brazil. It addresses the theoretical-conceptual, political-propositional and court-legal contributions pertinent to the construction of the right to the city, highlighting the specificity of the constitutional and infraconstutional texts produced in the sphere of the Constitution of the Federative Republic of Brazil of 1988 and of the City Statute. It recognizes contradictions between the constitutional prediction and the reality of denial of this right in Brazilian cities and between the understanding of the Master Plan as a space for participation and its concrete processes of institutionalization. In order to deepen the analysis, he considers the process of constituting the urban in the municipality of São Luís (Maranhão / Brazil), emphasizing aspects of the relationship between the State and the city materialized in the municipal public action regarding urban planning and the formulation of master plans. It delimits political subjects, institutional mediations and participatory experiences pertinent to the course (formulation, validity and revision) of the Participatory Master Plan of 2006, demarcating, through contradictions, inconsistencies, omissions, their meaning for the assertion of corporate-capitalist interests, weakening of popular participation and inefficiency as to the more substantive possibilities of realizing the right to the city. It concludes that, in the current historical conjuncture, the indications of the regressivity of the Brazilian State in the formulation of urban public policies and consolidation of institutions favorable to the realization of the right to the city are unequivocal. These are processes that even lessen legal institutes such as the Master Plan and amplify the challenges of political and professional subjects committed to the defense of social rights, especially the right to the city in Brazil.